Auditive and Vestibular Changes Related to the Use of Hydroxychlorochine and Chlorochine: An Integrative Review - Britto,Diana Babini Lapa de Albuquerque (2021)
Abstract Introduction The use of hydroxychloroquine and chloroquine is formally indicated in cases of chronic autoimmune diseases. However, the use of these medications has already been associated with possible transitory or definitive alterations in hearing function and/or vestibular function in humans, when administrated in the short and long terms. Objective To describe, through a literature analysis, the functional vestibular and/or hearing alterations, caused by the use of hydroxychloroquine and chloroquine in youths and adults. Data Synthesis In total, 2,481 studies were identified in the initial search: out of these 32 were selected for a full-text reading, and 9 were selected after the exclusion of those which did not meet the eligibility criteria. Of these, four articles pointed to the presence of vestibular and auditory-associated alterations, three indicated only auditory pathologies, and two, vestibular disorders. Regarding the auditory alterations, tinnitus was the most frequent symptom, and bilateral sensorineural hearing loss was described in most studies, varying in degree from mild to severe. As for the vestibular alterations, vertigo was the most reported symptom. Conclusion Knowledge of the auditory and vestibular effects after the use of these substances can help in the decision regarding the best treatment, enabling the consideration of other available therapies for patients at risk of suffering those alterations, reducing the risk of auditory and vestibular disorders.